The Role of Artificial Intelligence in Improving Athletic Performance: A Systematic Review - Sappar, Hasan; Ali , Basem; Asil, Fouad A.A. Al-Saady (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Abstract. The aim of this systematic review was to evaluate the impact of the use of artificial intelligence on improving athletic performance. Articles were selected through searches in various electronic databases, with those included following pre-established eligibility criteria. A narrative synthesis was performed. The electronic search resulted in 2,300 articles at first. After checking the titles, abstracts, and exclusion of duplicates, 52 were selected for full reading. After that, 33 articles were excluded. 19 articles were included in this systematic review. The included articles assess both the influence of artificial intelligence on improving team sports performance and individual sports performance. Forty percent of the articles found were observational, with the remaining 60% represented by quasi-experimental articles, indicating that few scientific methods were employed when testing interventions in the samples presented. The results indicate that the use of artificial intelligence has been more frequent in the study of team sports, with few studies using both commercial technologies. Studies demonstrate that despite the increase in research waves and the emergence of artificial intelligence products, many are still poorly understood. Moreover, the lack of proper control patterns also makes the comparison of results difficult. However, given the advances and the numerous possibilities for use, it is important to continue investing in research on artificial intelligence to improve the effectiveness and performance of athletes.